Light Co-coated N-PyC / MXene-BC wave-absorbing aerogel and preparation method thereof
Cover the dopamine and cobalt particles through the in -situ self -agglomeration effect, and form a method of nitrogen doping and thermal carbon layer, combined with bacterial cellulose to build three -dimensional gas gel, solving the complex and nitrogen doping distribution of the existing wave suction agent preparation method The problems of unevenness realize low -density and high loss of suction performance.
Patent Information
- Application Number
- CN202411228703.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-03
AI Technical Summary
The existing preparation methods for wave absorbers are complex, which easily lead to the fall of metal particles and the difficulty of uniform distribution of nitrogen doping, affecting the electromagnetic wave absorption performance of the material.
Use self-gathering and cooperation to cover dopamine and cobalt particles on the TI3C2TX matrix, and to form nitrogen doped thermal carbon layers by heat treatment, combined with bacterial cellulose to build three-dimensional gas gel, forming Co@n-Pyc/MXENE-BC suction Wave gel.
It achieves low-density, high-loss wave absorption performance, enhances dielectric loss capability, improves electromagnetic wave absorption performance, and reduces the density of the material.
Smart Images

Figure CN119350719A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of absorbing materials, and in particular to a lightweight Co@N-PyC / MXene-BC absorbing aerogel (lightweight nitrogen-doped Co confined catalytic Co@N-PyC / MXene-BC aerogel) and a preparation method thereof. Background Art
[0002] Since the advent of the wireless communication era, the application of electromagnetic waves has become popular. However, it has also brought about electromagnetic wave pollution, which has potential "harm" to human production and life. Therefore, it is particularly important to develop efficient and intelligent electromagnetic wave absorbing materials at present. Absorbing materials should have the performance characteristics of "light, thin, wide and strong". Absorbing materials with low density and strong loss characteristics have important application prospects. Due to the excellent properties of low density and high strength, porous lightweight electromagnetic absorbing materials have important application potential in the field of aircraft and aerospace. MXene (MXene-based two-dimensional titanium carbide (MXene)) is widely used in the field of electromagnetic absorption and shielding due to its excellent conductivity. Due to the small size of MXene nanosheets and weak interlayer interactions, it is difficult to construct a stable three-dimensional foam structure, but constructing a three-dimensional layered structure by various means is an effective way to make full use of highly conductive MXene nanosheets. Compared with MXene nanosheets, lightweight three-dimensional foams made of MXene nanosheets have low density, good flexibility, and porous structure, which provide good conditions for multiple reflections of electromagnetic waves.
[0003] Optimizing impedance characteristics is the key to achieving excellent electromagnetic wave absorption performance of materials. For high-loss materials such as MxeneTi3C2Tx, high conductivity will make the impedance of the material differ greatly from the spatial impedance, resulting in the reflection of electromagnetic waves. Therefore, it is necessary to select a low-loss medium to balance the high loss of Mxene and allow electromagnetic waves to enter the material as much as possible to optimize the absorption performance of electromagnetic waves. In addition, interface engineering is one of the effective strategies for regulating dielectric loss. It can enhance the attenuation ability of electromagnetic waves by regulating the mobility of charges between interfaces. Dopamine can self-polymerize to form polydopamine under aerobic conditions. Due to the presence of active groups such as hydroxyl groups on the surface of the coated material, polydopamine (PDA) can be attached to any matrix material. In addition, PDA has the property of forming coordination polymers with metal ions and can be used for in-situ deposition of metals without electrodeposition or co-deposition with metals. The coordination polymer can be converted into a highly conductive pyrolytic carbon nitrogen material (N-PyC) after high-temperature pyrolysis. Therefore, this strategy can be used to construct heterostructures to enhance dielectric loss capacity.
[0004] The existing preparation methods of absorbers usually use hydrothermal method or electrodeposition method to load metal particles onto the absorber matrix. The preparation process is complicated and easy to fall off. In addition, the introduction of nitrogen doping into the absorber usually uses an external nitrogen source. The preparation process is cumbersome, the introduced nitrogen content is difficult to control, and there is uneven distribution of components. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a lightweight Co@N-PyC / MXene-BC high-loss absorbing aerogel, which coats dopamine and cobalt particles on a Ti3C2Tx (titanium carbide) matrix through in-situ self-polymerization; after heat treatment, a nitrogen-doped pyrolytic carbon layer is formed on the surface, introducing a large number of defects; this not only enhances the dielectric loss, but also maintains a lower density, thereby achieving low-density, high-loss absorbing performance.
[0006] In order to solve the above technical problems, the technical solution adopted in this application is: a lightweight nitrogen-doped Co confined catalytic Co@N-PyC / MXene-BC aerogel, the material comprising: a Ti3C2Tx nanosheet matrix, a pyrolytic carbon layer and metal cobalt particles are coated on the Ti3C2Tx nanosheet matrix, and bacterial cellulose is added to assemble into Co@N-PyC / MXene-BC aerogel.
[0007] Furthermore, the density of the Co@N-PyC / MXene-BC aerogel is 20-30 mg / cm 3 .
[0008] Furthermore, the dielectric tangent (dielectric loss tangent) of the Co@N-PyC / MXene-BC aerogel is between 0.45 and 0.5.
[0009] The present application also provides a method for preparing the above-mentioned light nitrogen-doped Co confined catalytic Co@N-PyC / MXene-BC aerogel, and the preparation steps include:
[0010] (1) Dopamine and cobalt acetate were coated on the Ti3C2Tx matrix by an in-situ self-polymerization method to obtain a composite material;
[0011] (2) The composite material is then heat treated to convert the dopamine therein into nitrogen-doped pyrolytic carbon, and the cobalt acetate therein is pyrolyzed into metallic cobalt particles, which are uniformly coated on the surface of the Ti3C2Tx matrix to obtain the Co@N-PyC / MXene absorber;
[0012] (3) Then, bacterial cellulose (BC) is added to the absorber and mixed, and then water is added and stirred. After mixing, the lightweight Co@N-PyC / MXene-BC absorbing aerogel is obtained by freeze drying.
[0013] Furthermore, the in-situ self-polymerization in step (1) is specifically carried out as follows:
[0014] (1.1) freeze-drying the prepared few-layer Mxene Ti3C2Tx dispersion to obtain Ti3C2Tx powder nanosheets;
[0015] (1.2) Prepare a Tris HCl solution with a pH of 8 to 9, add dopamine powder and stir for 1 to 2 hours in the dark to obtain a uniformly dispersed dopamine solution;
[0016] (1.3) Add the powder prepared in step (1.1) to the dopamine solution in step (1.2), stir for 2-6 hours in a dark environment, and obtain a dispersed solution of Ti3C2Tx surface coated with dopamine;
[0017] (1.4) Add cobalt acetate to the dispersed solution obtained in step (1.3), continue stirring in the dark for 4-12 hours, repeatedly rinse the obtained solution with deionized water, and freeze-dry to obtain a powder of the composite material.
[0018] Furthermore, the preparation method of the few-layer Mxene Ti3C2Tx described in step (1.1) is: weigh Ti3AlC2:LiF with a mass ratio of 0.8-1.2:1, then add it to a mixture of hydrochloric acid and deionized water with a volume ratio of 2.5-3.5:1, stir the reaction at a temperature of 40-45°C for 24-48 hours, and then repeatedly wash with deionized water until the solution is neutral, and ultrasonicate the obtained solution for 2-3 hours to obtain a few-layer Ti3C2Tx dispersion (the few-layer Ti3C2Tx has high conductivity and a single layer is easy to form a conductive network).
[0019] Furthermore, in step (1.2), 10-30 mM Tris-HCl buffer is prepared from tris(hydroxymethyl)aminomethane and hydrochloric acid, the purpose of which is to provide an alkaline environment for the self-polymerization of dopamine.
[0020] Furthermore, the mass ratio of the Ti3C2Tx powder nanosheets and dopamine powder added in step (1.3) is 1 to 2:1.
[0021] Furthermore, the content of cobalt acetate magnetic particles loaded in the dispersed solution of dopamine coated on the surface of Ti3C2Tx described in step (1.4) is 2-8 mg / mL.
[0022] Furthermore, the specific operation process of step (2) is as follows: the composite material obtained in step (1) is subjected to heat treatment, wherein the dry powder is placed in a tubular furnace, the heat treatment temperature is 400-700°C, the heat treatment time is 1-2h, and Ar and H2 atmospheres are introduced during the heat treatment process for protection.
[0023] Furthermore, the specific operation process of the step (3) is as follows: adding bacterial cellulose, stirring and ultrasonicating for 25-35 minutes, pouring into a polytetrafluoroethylene mold, and freezing, demolding and drying for 48-72 hours to obtain Co@N-PyC / MXene-BC aerogel; after the addition is completed, the absorber Co@N-PyC / MXene accounts for 1.0wt.% to 2.5wt.% of the total mass of the mixed solution of the absorber, bacterial cellulose and water.
[0024] Furthermore, in step (3), the bacterial cellulose is a type of nanocellulose.
[0025] Advantages and beneficial effects of this application:
[0026] 1. The present application discloses a lightweight Co@N-PyC / MXene-BC absorbing aerogel, which has low density, strong dielectric loss capacity, and wide effective absorption bandwidth; the density of the Co@N-PyC / MXene-BC aerogel is 25 mg / cm 3 ; The dielectric tangent (dielectric loss tangent) of the Co@N-PyC / MXene-BC aerogel is about 0.48.
[0027] 2. This application uses in-situ self-polymerization to construct a multi-layer dielectric loss layer on a substrate, and builds multiple heterogeneous interface structures through interface engineering, namely pyrolytic carbon and crystalline carbon layers, metal particles and crystalline carbon layers, to promote dipole polarization and thus improve dielectric loss capacity.
[0028] 3. The buffer layer introduced on the surface of Ti3C2Tx in the present application refers to the coated nitrogen-doped pyrolytic carbon layer. Since the medium dielectric loss layer can effectively neutralize the high dielectric loss layer of Ti3C2Tx, the impedance mismatch is improved, allowing electromagnetic waves to enter the interior of the material as much as possible; it not only combines the rich functional groups on the surface of Ti3C2Tx, reduces the exposure of active sites and thus slows down the oxidation of Ti3C2Tx, but also the nitrogen-doped carbon layer formed by pyrolysis after heat treatment introduces a large number of defects in situ. The difference between the electronegativity of pyrrolic N and pyridinic N and the electronegativity of the surrounding carbon atoms leads to charge redistribution and enhanced dipole polarization, while the presence of graphitized N is conducive to enhancing electron migration and improving polarization and conductivity losses.
[0029] 4. The present application adopts a method of loading metal particles on an amorphous carbon layer. After pyrolysis, a crystalline carbon ring is precipitated around the amorphous carbon layer due to the confined catalytic effect of the metal, which promotes the movement and transition of electrons, enhances the conductivity loss, and improves the electromagnetic wave attenuation capability.
[0030] 5. In the present application, bacterial cellulose is selected as a binder to assemble the absorber into a three-dimensional macroscopic body. Although MXene contains abundant functional groups such as -OH and -O, it is negatively charged and cannot be directly assembled into a three-dimensional aerogel. The surface of bacterial cellulose contains a variety of organic functional groups. The assembly of the two not only solves the problem of easy stacking of two-dimensional MXene nanosheets, but also can construct a three-dimensional macroscopic body. The construction of the conductive network provides more reflection paths for electromagnetic waves and enhances the attenuation of electromagnetic waves. The aerogel obtained by freeze-drying has a lower density and better absorbing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a transmission electron microscope image of the Co@N-PyC / MXene absorber prepared in Example 1 of the present application;
[0032] Figure 2 The Raman spectrum of the Co@N-PyC / MXene absorber prepared in Example 1 of the present application;
[0033] Figure 3 This is a reflection loss diagram of the Co@N-PyC / MXene-BC aerogel prepared in Example 2 of the present application;
[0034] Figure 4 This is a reflection loss diagram of the N-PyC / MXene-BC aerogel prepared in comparative example 1 of the present application. DETAILED DESCRIPTION
[0035] The present invention will be further described in detail below in conjunction with specific examples, but the implementation methods of the present invention include but are not limited to the scope represented by the following examples.
[0036] The present application discloses a lightweight Co@N-PyC / MXene-BC high-loss absorbing aerogel; the aerogel is based on Ti3C2Tx, with a buffer layer and metal cobalt particles as an enhanced dielectric loss layer, and bacterial cellulose as a binder to assemble two-dimensional nanosheets into three-dimensional aerogels. The density of the aerogel is 25 mg / cm 3 , has strong loss performance and excellent wave absorbing performance, and the preparation method of the material specifically includes the following steps:
[0037] Embodiment 1:
[0038] (1) Weigh Ti3AlC2:LiF in a mass ratio of 1:1, then add it to a mixture of hydrochloric acid and deionized water in a volume ratio of 3:1, stir and react at a temperature of 40-45°C for 24-48 hours, then wash it repeatedly with deionized water until the solution is neutral, and ultrasonicate the obtained solution for 2-3 hours to obtain a few-layer Ti3C2Tx dispersion (the few-layer Ti3C2Tx has high conductivity and a single layer is easy to form a conductive network); then freeze-dry the prepared few-layer Mxene Ti3C2Tx dispersion to obtain Ti3C2Tx powder nanosheets; prepare pH = 8.5, 15mM Tris buffer, magnetically stir for 30 minutes, weigh 0.2g of dopamine powder and put it into the buffer, stir at room temperature for 2 hours in the dark; weigh the same mass of Ti3C2Tx powder nanosheets and add them, then ultrasonicate for 30 minutes to ensure that the nanosheets are evenly distributed in the solution, stir for 4 hours in the dark to obtain a mixed solution of Ti3C2Tx surface coated with polydopamine;
[0039] (2) The obtained mixed solution was cleaned with deionized water and ethanol by vacuum filtration, and the dopamine coating process in step (1) was repeated, followed by adding 4 mg / mL cobalt acetate particles and stirring for 4 h in the dark; a mixture of metal particles and polydopamine-coated Ti3C2Tx was obtained, which was repeatedly cleaned with deionized water and dried by freeze drying for 48 h to obtain a mixture powder;
[0040] (3) placing the obtained mixed powder into an atmosphere protection heat treatment furnace for heat treatment, wherein the gas introduced during the heat treatment process is a hydrogen / argon mixed gas, the hydrogen content is 20%, the gas flow rate is 20 ml / min, the heating rate is 5 ° C / min, the heat treatment temperature is 600 ° C, and the heat treatment time is 1 h to obtain a Co@N-PyC / MXene absorber;
[0041] (4) The absorber obtained in step (3) is mixed with bacterial cellulose in a mass ratio of 5:1, and then mixed with deionized water, wherein the mass fraction of the absorber in the total mixture is 2.5wt.%, and the mass fraction of BC is 0.5wt.% after mixing and stirring; ultrasonication is performed for 15 minutes, and the obtained mixed solution is poured into a polytetrafluoroethylene mold, and the Co@N-PyC / MXene-BC absorbing aerogel is obtained after freezing, demolding, and drying for 48 hours;
[0042] (5) The electromagnetic parameters of Co@N-PyC / MXene-BC absorbing aerogel were tested using the waveguide method, and the corresponding reflection loss was calculated and the results are shown in the attached figure. Figure 2 middle.
[0043] Figure 1This is the transmission electron microscope image of the Co@N-PyC / MXene absorber in Example 1. It can be seen that there are crystalline carbon rings on the pyrolytic carbon layer on the Ti3C2Tx substrate. This is because the catalytic effect of the metal cobalt particles converts the amorphous carbon around the cobalt particles into crystalline carbon.
[0044] Figure 2 The Raman spectrum of the Co@N-PyC / MXene absorber in Example 1 shows the typical D peak and G peak of carbon materials. D / I G The ratio is 1.6, indicating that the degree of crystallization is high after Ti3C2Tx is coated with pyrolytic carbon and loaded with Co particles.
[0045] Embodiment 2:
[0046] (1) Weigh Ti3AlC2:LiF in a mass ratio of 1:1, then add it to a mixture of hydrochloric acid and deionized water in a volume ratio of 3:1, stir and react at a temperature of 40-45°C for 24-48 hours, then wash it repeatedly with deionized water until the solution is neutral, and ultrasonicate the obtained solution for 2-3 hours to obtain a few-layer Ti3C2Tx dispersion (the few-layer Ti3C2Tx has high conductivity and a single layer is easy to form a conductive network); then freeze-dry the prepared few-layer Mxene Ti3C2Tx dispersion to obtain Ti3C2Tx powder nanosheets; prepare pH = 8.5, 15mM Tris buffer, magnetically stirred for 30 minutes, weighed 0.2g of dopamine powder and put it into the buffer, and stirred it at room temperature in the dark for 2 hours; weighed the same mass of Ti3C2Tx powder and put it into the dispersion liquid for ultrasonication for 30 minutes to ensure that the nanosheets are evenly distributed in the solution, and stirred it in the dark for 4 hours to obtain a mixed solution of Ti3C2Tx surface coated with polydopamine; the obtained mixed solution was cleaned with deionized water and ethanol by vacuum filtration;
[0047] (2) Then, 8 mg / mL cobalt acetate particles were added and stirred for 4 h in a dark environment; a mixture of metal particles and polydopamine-coated Ti3C2Tx was obtained, which was repeatedly washed with deionized water and dried by freeze drying for 48 h to obtain a mixture powder;
[0048] (3) placing the obtained powder into an atmosphere protection heat treatment furnace for heat treatment, introducing a hydrogen / argon mixed gas, a hydrogen content of 20%, a flow rate of 20 ml / min, a heating rate of 5 ° C / min, a heat treatment temperature of 600 ° C, and a heat treatment time of 1 h to obtain a Co@N-PyC / MXene absorber;
[0049] (4) The absorber obtained in step (3) was mixed with bacterial cellulose in a mass ratio of 5:1, and then mixed with deionized water and stirred. The mass fraction of the absorber in the total mixture was 2.5wt.%, and the mass fraction of BC was 0.5wt.%. Ultrasound was performed for 15 minutes, and the obtained mixed solution was poured into a polytetrafluoroethylene mold, and the Co@N-PyC / MXene-BC absorbing aerogel was obtained after freezing, demolding and drying for 48 hours.
[0050] Figure 3 The reflection loss capability of Co@N-PyC / MXene-BC absorbing aerogel in Example 2 is 10.1 dB, the thickness is 3.0 mm, the minimum reflection loss is -66.0 dB, and the effective absorption bandwidth in the X-band can reach 3.8 dB.
[0051] Comparative Example 1N-PyC / Mxene aerogel
[0052] In order to show the effect of metal particles on the dielectric properties of aerogels, the present application sets up a comparative example without adding metal particles. The method of Example 1 (excluding step (2)) is used to prepare N-PyC / Mxene aerogels. The electromagnetic parameters of the aerogels are tested using the waveguide method, and the corresponding reflection losses are calculated and the results are presented as the attached figure. Figure 4 From the figure, we can see that the thickness is 3.1mm, the frequency is 11.4GHz, the minimum RL value is -20.5dB, the dielectric loss capacity is weak, which is not conducive to meeting the impedance matching requirements, and the wave absorption performance is weak. This shows that when the metal particles are not loaded, the polarization and conductivity loss capacity are insufficient, resulting in a decrease in the wave absorption performance.
Claims
1. A lightweight Co@N-PyC / MXene-BC absorbing aerogel, characterized by: The material comprises: a Ti3C2Tx nanosheet matrix, a pyrolytic carbon layer and metal cobalt particles are coated on the Ti3C2Tx nanosheet matrix, and bacterial cellulose is added to assemble and form a Co@N-PyC / MXene-BC aerogel.
2. The lightweight Co@N-PyC / MXene-BC absorbing aerogel according to claim 1, characterized in that: The density of the Co@N-PyC / MXene-BC aerogel is 20-30 mg / cm 3 .
3. The lightweight Co@N-PyC / MXene-BC absorbing aerogel according to claim 1, characterized in that: The dielectric tangent of the Co@N-PyC / MXene-BC aerogel is 0.45-0.
5.
4. A method for preparing a lightweight Co@N-PyC / MXene-BC absorbing aerogel, characterized in that: The preparation steps include: (1) Dopamine and cobalt acetate were coated on the Ti3C2Tx matrix by an in-situ self-polymerization method to obtain a composite material; (2) The composite material is then heat treated to convert the dopamine therein into nitrogen-doped pyrolytic carbon, and the cobalt acetate therein is pyrolyzed into metallic cobalt particles, which are uniformly coated on the surface of the Ti3C2Tx matrix to obtain the Co@N-PyC / MXene absorber; (3) Then, bacterial cellulose is added to the absorbent and mixed, and then water is added and stirred. After mixing, the lightweight Co@N-PyC / MXene-BC absorbing aerogel is obtained by freeze drying.
5. The method for preparing the lightweight Co@N-PyC / MXene-BC absorbing aerogel according to claim 4, characterized in that: The step (1) is in-situ self-polymerization, and the specific operation process is as follows: (1.1) freeze-drying the prepared few-layer Mxene Ti3C2Tx dispersion to obtain Ti3C2Tx powder nanosheets; (1.2) Prepare a Tris HCl solution with a pH of 8 to 9, add dopamine powder and stir for 1 to 2 hours in the dark to obtain a uniformly dispersed dopamine solution; (1.3) Add the powder prepared in step (1.1) to the dopamine solution in step (1.2), stir for 2-6 hours in a dark environment, and obtain a dispersed solution of Ti3C2Tx surface coated with dopamine; (1.4) Add cobalt acetate to the dispersed solution obtained in step (1.3), continue stirring in the dark for 4-12 hours, repeatedly rinse the obtained solution with deionized water, and freeze-dry to obtain a powder of the composite material.
6. The method for preparing the lightweight Co@N-PyC / MXene-BC absorbing aerogel according to claim 5, characterized in that: The preparation method of the few-layer Mxene Ti3C2Tx described in step (1.1) is: weigh Ti3AlC2:LiF with a mass ratio of 0.8-1.2:1, then add it to a mixed solution of hydrochloric acid and deionized water with a volume ratio of 2.5-3.5:1, stir the reaction at a temperature of 40-45°C for 24-48h, then repeatedly wash with deionized water until the solution is neutral, and ultrasonicate the obtained solution for 2-3h to obtain a few-layer Ti3C2Tx dispersion.
7. The method for preparing the lightweight Co@N-PyC / MXene-BC absorbing aerogel according to claim 5, characterized in that: In step (1.2), 10-30 mM Tris-HCl buffer is prepared from tris(hydroxymethyl)aminomethane and hydrochloric acid.
8. The method for preparing the lightweight Co@N-PyC / MXene-BC absorbing aerogel according to claim 5, characterized in that: The mass ratio of the Ti3C2Tx powder nanosheets and dopamine powder added in step (1.3) is 1 to 2:
1.
9. The method for preparing the lightweight Co@N-PyC / MXene-BC absorbing aerogel according to claim 5, characterized in that: The content of cobalt acetate magnetic particles loaded in the dispersed solution of dopamine coated on the surface of Ti3C2Tx described in step (1.4) is 2-8 mg / mL.
10. The method for preparing the lightweight Co@N-PyC / MXene-BC absorbing aerogel according to claim 4, characterized in that: The specific operation process of the step (2) is as follows: the composite material obtained in step (1) is subjected to heat treatment, wherein the dried powder is placed in a tubular furnace, the heat treatment temperature is 400-700°C, the heat treatment time is 1-2h, and Ar and H2 atmospheres are introduced during the heat treatment process for protection.
11. The method for preparing the lightweight Co@N-PyC / MXene-BC absorbing aerogel according to claim 4, characterized in that: The specific operation process of the step (3) is as follows: adding bacterial cellulose, stirring and ultrasonicating for 25-35 minutes, pouring into a polytetrafluoroethylene mold, and freezing, demolding and drying for 48-72 hours to obtain Co@N-PyC / MXene-BC aerogel; after the addition is completed, the absorber Co@N-PyC / MXene accounts for 1.0wt.% to 2.5wt.% of the total mass of the mixed solution of the absorber, bacterial cellulose and water.
12. The method for preparing the lightweight Co@N-PyC / MXene-BC absorbing aerogel according to claim 4, characterized in that: The bacterial cellulose in step (3) is a type of nanocellulose.
Citation Information
Patent Citations
MXene-polydopamine composite material and preparation method thereof
CN109096754A
Preparation method of MXene / cellulose composite aerogel
CN109679146A
Surface coating modified metal powder material, preparation method thereof and wave-absorbing material
CN116239994A
Nitrogen-doped graphene aerogel / epoxy resin composite wave-absorbing material and preparation method thereof
CN117402461A
Cited By
Cotton-derived carbon fiber / MXene / TiO2 multifunctional composite aerogel material and preparation method thereof
CN120208240A